Pengaruh Strategi Pembelajaran dan Kecerdasan Interpersonal Terhadap Hasil Belajar Ilmu Pengetahuan Sosial Setelah Mengontrol Kemampuan Awal Siswa - -, Nurdiansyah (JTP - Jurnal Teknologi Pendidikan, 2017)
This study aims was to determined the effect of instruction strategies and interpersonal intelligences towards learning outcomes of social science, after controlling entry behavior. The participants were 35 students were divided into two treatment classes. This study uses a experimental method with treatment by level 2x2. Data analysis was Analysis of Covariat (ANCOVA). The results showed that: the value Fhitung = 15.27 > Ftable (Î± = 0.05) (31) = 4.20. Thus concluded that there are differences in outcomes between of students to learn social science taught by Problem Based Learning (A1) with a students who are taught by a Direct Instruction (A2) after controlling entry behavior. The conclusion of this study is the result of learning outcome social science between of students was given a Problem Based Learning was higher than the students who were given Direct Instruction after controlling entry behavior.